Biogeoquímica da Várzea do Lago Grande de Curuai, Rio Amazonas, Pará, Brasil: caracterização, origem, ciclagem e destino do material orgânico e inorgânico - Pérez, Marcela Andrea Pérez (2008)
The aim of this work was to study the biogeochemistry of a floodplain system in the Amazon lowland. The Lago Grande of Curuai floodplain is located on the right bank of the river near to Óbidos city, in the Pará state to 850 km of the Atlantic Ocean. The system is composed of more than 30 lakes of black and white waters, connected to each other and to the Amazon. This study consisted into determine the origin, the characterization and the cycling processes of major organic and inorganic elements within the system and its role in the transport of material into the river. Variations in the water level in the floodplain accompanying the Amazon ones, in which the hydrological cycle consists of a period of high waters between May and June, and a period of low water between October and November. Seven campaigns were conducted from 2004 to 2006 in different hydrological periods: rising, high, low and falling waters. The samples were taken for particulate and dissolved matter analysis. Temperature (T), pH, conductivity and dissolved oxygen (DO) were measured in situ. In the particulate matter were determined: organic carbon (POC), total nitrogen (PTN), δ13C and δ15N isotopes, total suspended solids (TSS). In the dissolved matter were analyzed: organic carbon (DOC) and inorganic (DIC), organic nitrogen (DON) and inorganic (NH4 +, NO2 - and NO3 -), and organic phosphorus (DOP) and inorganic (PO4 3-). The dissolved matter was also characterized by fractions hydrophobic (HPO) and transphilics (TPH) from the parameters: DOC, DON, δ13C and δ15N, specific ultraviolet absorbance to 254 nm (SUVA), reactivity (carboxylic and hydroxylic groups) and molecular weight (MW). To identify the most reactive dissolved organic matter, sorptions experiments were conducted between the fractions HPO and TPH and a mineral mixture of Kaolinite and Goethite (84.6 e 15.4%, respectively). The Curuai floodplain is a very productive system and limited by the dissolved inorganic nitrogen (DIN) that presented a N/P rate between 4,51 and 12,80. Recycling processes work intensively during the hydrological cycle (δ15N de 6,03 ± 2,55, in the white water lakes). The autochthonous produced during the rising and initial high water is dominated by phytoplankton (C/Chla de 116,35 ± 116,39) and exported to the Amazon River during falling waters. While, in the lower water is observed the demineralization of the MPS. The HPO and TPH fractions of the DOM presented molecular weight (MW) ~448 Da, and predominance of carboxylic groups. The major fraction HPO that was sorpted onto mineral particles has more aromaticity and it is rich in carbon. The floodplain works as an exporter of both particulate and dissolved organic matter (POM and DOM, respectively) to the Amazon. In 2004 the Curuai floodplain exported to Amazon River 64.990 ton POC and 12.008 ton PON. It is also exported 52.824 ton DOC and 8.093 ton DON.